Locality and Growth of Mysore Gum - Singh, S. P. (Indian Forester, 1979)
Mysore gum plantations have wide range of distribution. But on account of change in soil and climate, their growth is not same all Over Use has been made of dummy variables in multiple regression to group entire distribution into few similar regions of growth and yield. Estimates based on regions so delineated would be more accurate and explain variation in population from which they are drawn better than any haphazard attempt.